INVENTARISASI ANGGREK EPIFIT DI KEBUN RAYA EKA KARYA BALI - IG. Tirta; Sutomo Sutomo (Pusbindiklat - LIPI, 2014)
Inventory of epiphyte orchid species was conducted at Eka Karya Bali Botanic Garden on 26 September to17 October, 2009. The host trees were selected randomly (purposive randomized sampling), especially selected host trees for epiphyte orchid. The results showed that there were 34 known species of orchids belonging to 14 genera. Bulbophyllum was the highest number of species (seven species). Generally, epiphytic orchids grew on thin substrate with light intensity and mostly on zone IV. There were 162 species as host trees, which were dominated by Prunus puddum Roxb. ex Wall., Araucaria bidwillii Hook., Toona sureni (Blume) Merr., Syzygium racemosum (Blume) DC., and Syzygium zollingerianum (Miq.) Amsh.